1×2=
(1×2×3-0×1×2);
2×3=
(2×3×4-1×2×3);
3×4=
(3×4×5-2×3×4);
…
10×11=
(10×11×12-9×10×11);
…
n×(n+1)=
[n×(n+1)×(n+2)-(n-1)×n×(n+1)].
(1)1×2+2×3+3×4+…+10×11
=
(1×2×3-0×1×2)+
(2×3×4-1×2×3)+
(3×4×5-2×3×4)+…+
(10×11×12-9×10×11)
=
(10×11×12)=440;
(2)1×2+2×3+3×4+…+n×(n+1)
=
(1×2×3-0×1×2)+
(2×3×4-1×2×3)+
(3×4×5-2×3×4)+…+
[n×(n+1)×(n+2)-(n-1)×n×(n+1)]=
[n×(n+1)×(n+2)];
(3)1×2×3=
(1×2×3×4-0×1×2×3);
2×3×4=
(2×3×4×5-1×2×3×4);
3×4×5=
(3×4×5×6-2×3×4×5);
…
7×8×9=
(7×8×9×10-6×7×8×9);
∴1×2×3+2×3×4+3×4×5+…+7×8×9
=
(1×2×3×4-0×1×2×3)+
(2×3×4×5-1×2×3×4)+
(3×4×5×6-2×3×4×5)+…+
(7×8×9×10-6×7×8×9);
=
(7×8×9×10)=1260.